Audit Aplikasi BMKGSOFT V2 Berbasis Framework COBIT 2019 pada BMKG Provinsi Lampung - Robin Hoky; Joko Triloka (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2025)
Law Number 31 of 2009 states that the enhancement of economic growth, defense, security, and the protection of lives and property all heavily depend on meteorological, climate, and geophysical (MCG) information. Therefore, proper management of MCG data is crucial to prevent obstacles in the adoption of such information. As part of the next stage in implementing BMKG’s e-Government initiative, BMKGSoft V2 was introduced as an integrated and centralized online data management system to facilitate data access. However, in practice, the implementation of BMKGSoft V2 has been inconsistent, as evidenced by several issues. This study aims to audit the governance of the BMKGSoft V2 data management system using the COBIT 2019 framework, specifically the MEA01, MEA02, and MEA03 domains, to determine the extent to which system performance objectives have been achieved, conduct a gap analysis, and provide recommendations for development. The results show that the MEA01, MEA02, and MEA03 domains have achieved a capability and maturity level of 4 (Predictable Process), indicating that the BMKGSoftdata management system has well-defined IT procedures to achieve its objectives, and its performance can be quantitatively compared to established standards.